Neurocognitive functioning and cerebrovascular reactivity after carotid endarterectomy. (23rd January 2018) - Lattanzi, Simona; Carbonari, Luciano; Pagliariccio, Gabriele; Bartolini, Marco; Cagnetti, Claudia; Viticchi, Giovanna; Buratti, Laura; Provinciali, Leandro; Silvestrini, Mauro
Abstract : Objective: To evaluate in patients with TIA and ipsilateral high-grade internal carotid artery (ICA) stenosis whether changes in cognitive performance and cerebral hemodynamics occurred after carotid endarterectomy (CEA) and to explore their relationship. Methods: Participants were patients who underwent CEA, had TIA within the last 6 months, and had an ipsilateral severe ICA stenosis. Coloured Progressive Matrices (CPM) plus Complex Figure Copy Test (CFCT) and phonemic (ph) plus categorical (ca) Verbal Fluency (VF) tests were performed to assess right and left hemisphere cognitive functions, respectively. Hemodynamics was assessed with transcranial Doppler ultrasonography by means of the cerebral vasomotor reactivity (CVR) to hypercapnia. Results: A total of 137 patients were included. Before CEA, patients with right ICA obtained lower scores on the CPM and CFCT; patients with left ICA stenosis performed worse on the phonemic and categorical VF tests. The CVR was decreased on the side of the stenosis. At 6 months from CEA, CVR and cognitive performance were significantly improved. The performance change in cognitive tests exploring the revascularized hemisphere was positively associated with the ipsilateral CVR variation (CPM: R 2 for linear regression = 0.759, adj R 2 = 0.737; CFCT: R 2 = 0.734, adj R 2 = 0.710; (ph)VF: R 2 = 0.774, adj R 2 = 0.749; (ca)VF: R 2 = 0.732, adj R 2 = 0.703). Conclusion: Cognitive performance was enhanced at 6 months since CEA, and the improvement was related to the CVR increase. Cerebral hemodynamics may be an independent and potentially reversible determinant of cognitive dysfunction in severe carotid artery disease.